Verbos de elocução: um estudo baseado em frames - Kohlrausch, Maristela Maria (Universidade do Vale do Rio do Sinos, 2009)
This study is linked to a larger research project (CHISHMAN, 2007) and aims to make a computer-semantic Portuguese lexicon investigation of the communication verbs. The theoretical and methodological approach used is Frame Semantics (Fillmore 1982, 1985), which is inserted in the field of Cognitive Linguistics. In the perspective of Frame Semantics the FrameNet database was created, which presents the possible semantic and syntactic (valences) combination for each word, with each of its senses. This paper presents a proposal for a study of the communication verbs from this paradigm, and this choice is justified because these verbs are a class that expresses a series of semantic nuances, such as the subjectivity and expression of emotion, allowing different perspectives related to its study. Besides the theorical view, we present an empirical study which includes the syntactic-semantic description of ten communication verbs. For the compilation of the corpus, we used Sketch Engine tool. The results showed that
Keywords: FrameNet; verbos de elocução; semântica de frames; communication verbs; frame semantics; Letras e Artes; Lingüística